Pelatihan Mobile Robot Pengikut Garis: Upaya Peningkatan Minat Siswa SMP terhadap Robotika - Rendyansyah, Rendyansyah; Hikmarika, Hera; Caroline, Caroline; Rahmawati, Rahmawati; Hermawati, Hermawati; Bayusari, Ike (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This line-following mobile robot training program aims to foster junior high school students' interest and motivation in robotics, equip them with basic knowledge and skills, and encourage the development of sustainable robotics learning in schools. Methodology: This training method involves preparation stages, socialization and selection of participants, implementation of interactive learning, starting with the basics of robotics and moving on to programming and testing, evaluating student results and interests, and further mentoring, including forming a robotics club. Results: The training increased student enthusiasm and participation, strengthened conceptual understanding and skills in assembling and programming robots, and positively impacted students' technical and soft skills. Conclusions: This training effectively improves junior high school students' digital literacy and robotics skills with structured and fun methods, while supporting the development of sustainable robotics learning in schools. Limitations: Limitations include the limited number of tools, short training time, variation in student abilities, and incomplete evaluation of soft skills and long-term impacts. Contribution: This program increases students' interest, knowledge, and robotics skills, builds an innovative technology learning culture, and becomes a learning model for further activities.